2019
DOI: 10.3390/f10111009
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Landslide Activity Using Dendrogeomorphological Analysis in the Karavanke Mountains in NW Slovenia

Abstract: Tree ring eccentricity was used to reconstruct landslide activity in the last 138 years in the Urbas landslide located at Potoška planina in the NW part of the Karavanke Mountains, Slovenia. The research was based on the dendrochronological sampling of Norway spruce (Picea abies (L.) Karst.) in areas of varying landslide intensity. Analysis of a sudden change in the eccentricity index of 82 curved trees concluded that there were 139 growth disturbances and 16 landslide reactivations between 1880 and 2015, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The surveys revealed that the Urbas landslide is a composite landslide (Cruden & Varnes, 1996) consisting of rock falls (upper part), deep-seated landslides (main body) and debris flow source areas (lower part) (Peternel, 2017;Peternel et al, 2017a). The long-term activity of the Urbas landslide over the past 138 years has also been reconstructed using the dendrogeomorphological analysis of bent trees (Oven et al, 2019). Dendrogeomorphology has proven to be a highly useful method in the study of past slope mass movements and has recently been applied to the analysis of the debris flood magnitude in the Planica valley (Novak et al, 2020).…”
Section: An Overview Of Past Researchmentioning
confidence: 99%
“…The surveys revealed that the Urbas landslide is a composite landslide (Cruden & Varnes, 1996) consisting of rock falls (upper part), deep-seated landslides (main body) and debris flow source areas (lower part) (Peternel, 2017;Peternel et al, 2017a). The long-term activity of the Urbas landslide over the past 138 years has also been reconstructed using the dendrogeomorphological analysis of bent trees (Oven et al, 2019). Dendrogeomorphology has proven to be a highly useful method in the study of past slope mass movements and has recently been applied to the analysis of the debris flood magnitude in the Planica valley (Novak et al, 2020).…”
Section: An Overview Of Past Researchmentioning
confidence: 99%
“…In the last decades, several site investigations and monitoring projects have been carried out in the wider landslide-prone area (Mikoš et al, 2008;Jež et al, 2008;Komac et al, 2014;Oven et al, 2019;Peternel et al, 2018;Janža et al, 2018;Jemec Auflič et al, 2019;Šegina et al, 2020). For a detailed overview of the investigations see Peternel et al (2022).…”
Section: Study Areamentioning
confidence: 99%
“…Dendrogeomorphology has proven to be a highly useful method in studies of past slope mass movements. Oven et al (2019) reconstructed landslide activity over the past 138 years using dendrogeomorphological analysis in the form of tree ring eccentricity in the Karavanke Mountains in NW Slovenia -on the Urbas Landslide at Potoška Planina above the settlement of Koroška Bela. Novak et al (2020) developed a method that directly estimates the magnitudes of past debrisflood events on an alluvial fan using dendrogeomorphological and meteorological data sets.…”
Section: Debris-flow Magnitudesmentioning
confidence: 99%
“…, Jemec Auflič (2012), Komac et al (2012), Žibert et al (2012), Baron et al (2013), Komac et al (2015), Peternel et al (2017), Šegina et al(2020)Estimation of debris-flow magnitudesSodnik and Mikoš (2006a;2006b),Šmuc et al (2015),Sodnik et al (2017),Novak et al (2018),Sodnik et al (2018a;2018b),Oven et al (2019),Novak et al (2020) …”
mentioning
confidence: 99%